Role of abnormal microRNA expression in Helicobacter pylori associated gastric cancer. (4th March 2019) - Zou, Dan; Xu, Ling; Li, Heming; Ma, Yanju; Gong, Yuehua; Guo, Tianshu; Jing, Zhitao; Xu, Xiuying; Zhang, Ye
Abstract: Epidemiological studies have shown that Helicobacter pylori (HP) infection is a risk factor for gastric cancer (GC). HP infection may induce the release of pro-inflammatory mediators, and abnormally increase the level of reactive oxygen species (ROS), nitric oxide (NO), and cytokines in mucosal epithelial cells of the stomach. However, the specific mechanism underlying the pathogenesis of HP-associated GC is still poorly understood. Recent studies have revealed that abnormal microRNA expression may affect the proliferation, differentiation, and apoptosis of mucosal epithelial cells of the stomach to further influence GC occurrence, development, and metastasis. Herein, we summarize the role of abnormal microRNAs in the regulation of HP-associated GC progression. Abnormal microRNA expression in HP-positive GC may be a biomarker for GC diagnosis, occurrence, and development as well as its targeted treatment and prognosis.